The nassariids from the Gulf of Gabès revisited (Neogastropoda, Nassariidae). Issue 4 (21st April 2017) - Aissaoui, Chrifa; Galindo, Lee Ann; Puillandre, Nicolas; Bouchet, Philippe
ABSTRACT: Since the latter half of the nineteenth century, marine biologists have recognized that many molluscs living in the Gulf of Gabès, on the southern coast of Tunisia, exhibit a number of morphological characters that set them apart from the 'typical form or variety' that occurs in the rest of their Mediterranean distribution area. In the family Nassariidae, local forms (varieties or subspecies) were recognized as early as 1882, but none of these is currently recognized as having taxonomical significance. We have revisited the species-level systematics of the family using an integrative approach, based on morphological, geographic and molecular evidence (COI and 28S). Besides Tritia gibbosula (not sampled by us), we delimitated seven species, three with a broad range: Tritia neritea (probably introduced), T. mutabilis (but with considerable genetic structure between localities), and T. corniculum ; and four not previously recognized as valid, and which may be considered Gulf of Gabès endemics: T. lanceolata, T. tenuicosta, T. pallaryana sp. nov. and T. djerbaensis sp. nov. Also, Tritia elongata is recognized as a valid species in the T. corniculum complex, with a distribution outside the Gulf of Gabès. It is remarkable that all have paucispiral protoconchs indicating non-planktotrophic larval development. http://zoobank.org/urn:lsid:zoobank.org:pub:069F3B3B-66E8-4C07-A974-3023924426EB